The Influence of Different Seeding Application Rates and Sowing Time on Maize Hybrids’ Productivity in the Conditions of the Republic of Bashkortostan’s Southern Forest-Steppe Zone - Bulat Akhiyarov; Igor Kuznetsov; Rail Alimgafarov; Damir Islamgulov; Rishat Abdulvaleyev (Applied and Environmental Soil Science)
Maize takes the leading place in yield and is one of the most common crops in the world. Selection of the optimal seeding application rate and time is among the central issues in maize cultivation technology and is highly relevant. The research made in 2018–2020 aimed at improving the maize technology block for grain (seeding application rate and sowing time, southern forest-steppe, the Republic of Bashkortostan). For this purpose, a field experiment was launched in a fourfold replication. The experimental design included hybrids: Nur, Mashuk 171, Baikal and Mashuk 220 with a planting density of 60 (control), 70, 80, and 90 thousand pcs/ha. The experiment revealed a high correlation dependence of the yield of green mass and grain on the sowing time (r = 0.876–0.915 and r = 0.951–0.963). In the conditions of the Republic of Bashkortostan’s southern forest-steppe, Baikal and Mashuk 171 hybrids are recommended to be used for animals and poultry diets and the planning of maize cultivation technological schemes at early sowing time (May 10) and a seeding application rate of 80 thousand pcs/ha. The results of the research apply to the formation of agricultural feeding diets.